Chapter 10. Minor Vegetable Crop Production - Dakshina Seal; Qingren Wang; Ramdas Kanissery; Eugene J. McAvoy; Crystal A. Snodgrass; Julien Beuzelin; Johan Desaeger; Nicholas Dufault; Shouan Zhang (EDIS, 2022)
Chapter 10 of the Vegetable Production Handbook.